Body Shaming dalam Perspektif Hadis: Kajian atas Fenomena Tayangan Komedi di Layar Televisi - Umaroh, Dewi; Bahri, Samsul (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This paper examines the phenomenon of body shaming which becomes content in comedy on television screens even though in the hadith it is clear that there is a prohibition againts body shaming. This paper is a library research using qualitative methods and the theory used is the science of ma'anil hadis namely the science that discusses how to properly understand a text of hadith by considering various aspects in it. The results obtained from this study are: first, body shaming is the act of commenting on a person's physical appearance or appearance and first appeared around the 1900s in the United States. Second, there are two traditions which prohibit body shaming, namely the hadith about Sahabats who laughed at Ibn Mas'ud's small calf and Aisyah's hadith which calls Shofiyyah a short woman. Third, there are four conditions for allowing comedy as conveyed by Imam Nawawi, namely not to overdo it, not to hurt other people's feeling, not to trigger hatred and not to lower the prestige of others. Based on the two hadith above and the comedy requirement of Imam Nawawi, comedy whose content contains body shaming is not allowed, whereas comedy in general without any elements of body shaming ot other prohibited elements is still allowed.